Pengaruh Transparansi dan Akuntabilitas Pengelolaan Dana Zakat Terhadap Peningkatan Jumlah Muzakki Dalam Membayar Zakat Di Lembaga Amil Zakat (LAZ) Inisiatif Zakat Indonesia(IZI) - Nia Anggriani; Andi Harpepen; Asnaini Asnaini (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2026)
This study aims to determine the effect of transparency and accountability in zakat fund management on increasing the number of muzakki in paying zakat at the Indonesian Zakat Initiative Amil Zakat Institution. The problem in this study is based on the importance of public trust in zakat management institutions, which can be built through transparency and accountability in managing zakat funds. This study uses a quantitative approach with an associative research type. The data used are primary data obtained through distributing questionnaires to respondents. The sampling technique used in this study is the slovin method, with a total of 75 respondents. The data analysis techniques used are the t test and f test. The results of the study indicate that transparency and accountability in zakat fund management influence the increase in the number of muzakki in paying zakat at AZ IZI Bengkulu, both partially and simultaneously. The better the transparency and accountability implemented by the institution, the greater the public's trust and interest in distributing zakat through the institution.